LAPLACE-BELTRAMI OPERATOR OF A HELICOIDAL HYPERSURFACE IN FOUR-SPACE - Guler, Erhan; Magid, Martin; Yayli, Yusuf (Bulgarian Acad Sciences, Inst Mechanics, 2016)
We introduce helicoidal hypersurface in the four dimensional Euclidean space. We calculate the mean and the Gaussian curvature, and some relations of the helicoidal hypersurface. Then we give the Laplace-Beltrami operator of the helicoidal hypersurface.
Keywords: Gaussian Curvature; Helicoidal Hypersurface; Laplace-Beltrami Operator; Mean Curvature